Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters - Oliveira, Otto M. P.; Miranda, Thaís P.; Araujo, Enilma M.; Ayón, Patricia; Cedeño-Posso, Cristina M.; Cepeda-Mercado, Amancay A.; Córdova, Pablo; Cunha, Amanda F.; Genzano, Gabriel N.; Haddad, Maria Angélica; Mianzan, Hermes W.; Migotto, Alvaro E.; et al. (Zootaxa, 2016)
We have compiled available records in the literature for medusozoan cnidarians and ctenophores of South America. New records of species are also included. Each entry (i.e., identified species or still as yet not determined species referred to as “sp.” in the literature) includes a synonymy list for South America, taxonomical remarks, notes on habit, and information on geographical occurrence. We have listed 800 unique determined species, in 958 morphotype entries: 5 cubozoans, 905 hydrozoans, 25 scyphozoans, 3 staurozoans, and 20 ctenophores. Concerning nomenclatural and taxonomical decisions, two authors of this census (Miranda, T.P. & Marques, A.C.) propose Podocoryna quitus as a nomen novum for the junior homonym Hydractinia reticulata (Fraser, 1938a); Euphysa monotentaculata Zamponi, 1983b as a new junior synonym of Euphysa aurata Forbes, 1848; and Plumularia spiralis Milstein, 1976 as a new junior synonym of Plumularia setacea (Linnaeus, 1758). Finally, we also reassign Plumularia oligopyxis Kirchenpauer, 1876 as Kirchenpaueria oligopyxis (Kirchenpauer, 1876) and Sertularella margaritacea Allman, 1885 as Symplectoscyphus margaritaceus (Allman, 1885).